EVALUASI KEMAMPUAN ALAMI WILAYAH DALAM KONSERVASI AIR DAN PENGENDALIAN BANJIR - Alinda Medrial Zain (Jurnal Teknologi Lingkungan, 2006)
Urban green space plays several roles in balancing the urban ecosystem and maintaining the environment sustainability. Firstly, the urban green space plays a valuable role in prevention of flooding. Trees restrain the movement of sediment and run off. Secondly, the urban green space plays an important role in water conservation, since the tree’s roots absorb some excess water from the soil, making the soil drier, and are able to store morerainwaters. Therefore, the analysis of natural capability of a region in water conservation and flood prevention should become the basis to produce sustainable spatial planning. A study of the importance of green space in maintaining environmental balance in Batam, Malang and Muaro Jambi were conducted by P4W-IPB and P3TL-BPPT by applying the Kato model withsome slightly modifications, to map and evaluate the natural capability of those areas on water conservation and flood prevention. The model is based on validated land evaluation models and ecological value, and mapping the differences between the land covered by green space and that by abandoned areas. Evaluation of the ecological functions of urbangreen space, in combination with other parameters, has been done under GIS and Remote Sensing. The spatial analysis of the ecological function within three areas showed different figures, in which the that 38.12 % of Muaro Jambi, 35.22 % of Malang and 13.36 % of Batam, were functioning properly for water conservation, while 57.71 % of Muaro Jambi, 37.01 % of Malang and 23.75 % of Batam were functioning properly for flooding prevention.